Karakteristik Buah Melon (Cucumis melo L.) pada Lima Stadia Kematangan - Huda, Amalia Nurul; Suwarno, Willy Bayuardi; Maharijaya, dan Awang (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Melon breeding for fruit quality improvement is important to produce new varieties that meet consumers’ demand. The aim of this study was to elucidate the fruit characteristics of melon at five different maturity stages, involving several genotypes belonging to two cultivar groups: reticulatus and inodorus. The experiments were conducted in three planting seasons: (1) January-March 2015 (13 genotypes), (2) December 2015-February 2016 (56 genotypes), (3) February-May 2016 (9 genotypes). These trials were conducted at the Tajur II experimental station of IPB, Bogor, and each trial was arranged in a single factor randomized complete block design with three blocks. Maturity stages was determined based on fruit rind color and net coverage, and their effects on fruit quality were studied using combined analyses over seasons. Maturity stage significantly affected the fruit length, fruit diameter, flesh thickness, fruit weight, and sugar content. The average weight of the fruits at maturity stage 4 (838.90 g) and 5 (931.79 g) was significantly greater than that of stage 1 (584.42 g). The sugar content increased from maturity stage 2 (5.51 oBrix) to 3 (6.13 oBrix) and to 5 (8.18 oBrix). Fruit weight significantly correlated with fruit length (r = 0.53), fruit diameter (r = 0.85), fruit rind thickness (r = 0.33), and flesh thickness (r = 0.63). Maturity stages affected the quality of melon fruits, and therefore the determination of appropriate harvesting criteria is important in melon cultivations.Keywords: cantalupensis, correlation, inodorus, fruit quality, skin colour